In vitro synergistic antifungal activities of caspofungin in combination with fluconazole or voriconazole against Candida species determined by the Etest method. (September 2022) - Yang, Qianting; Liu, Zhiyong; Wang, Yan; Xie, Jiao; Zhang, Kanghuai; Dong, Yalin; Wang, Yun F.
Highlights: Etest method is useful for in vitro testing of combination antifungal therapy. A combination of caspofungin and triazoles was effective for Candida infections. Caspofungin and triazole combination was effective for Candida. glabrata with FKS mutation. Abstract: Objectives: Increased resistance of Candida species, especially Candida. glabrata is problematic. Combination antifungal therapies were studied to solve the problem. Methods: In this study, combinations of caspofungin with fluconazole and voriconazole were evaluated in 28 Candida species (including 15 C. glabrata and 12 with FKS mutation) at 24 and 48 hours using two Etest methods (direct cover method and MIC/MIC method). Results: For Candida isolates, direct cover method showed synergy of caspofungin-fluconazole and caspofungin-voriconazole against 12/28 (43%) isolates at 24 hours, and against 16/28 (57%) isolates at 48 hours. The MIC/MIC method showed synergy of caspofungin-fluconazole and caspofungin-voriconazole against 11/28 (39%) and 12/28 (43%) isolates at 24 hours, and against 16/28 (57%) and 17/28 (61%) isolates at 48 hours, respectively. For C. glabrata, direct cover method showed synergy of caspofungin-fluconazole and caspofungin-voriconazole against 11/15 (73%) and 10/15 (67%) isolates at 24 hours, and 11/15 (73%) and 13/15 (87%) isolates at 48 hours, respectively. The MIC/MIC method showed synergy of caspofungin-fluconazole and caspofungin-voriconazole against both 11/15 (73%) isolates at 24 hours, and 10/15 (67%) and 14/15 (93%) isolates at 48 hours, respectively. Conclusion: A combination of caspofungin and fluconazole or voriconazole might be effective against infections caused by Candida species, especially C. glabrata with FKS mutation.